India's Progress towards the health related Millennium Development Goals – Maternal Health - I, Patel; J, Chang; J, Srivastava; I, Patel; R, Balkrishnan (Indian Journal of Pharmacy Practice)
With a significant percentage of world population in India, global emphasis on improving maternal health in India has increased. Though India has made some progress in reducing the maternal mortality rate, it is still far from the MDG target. From a structural perspective, the slow progress towards more efficient maternal health care is rooted in issues like inadequate manpower, infrastructure and other resources like medicines and emergency facilities. However, the problem may have deeper roots in the socio political environment in India. These may be manifested in the lack of political and social will to focus on maternal healthcare, social perceptions of grass root healthcare workers like 'auxiliary nurse midwives', and prioritized attention to population control initiatives like family planning. This article presents an overview and analysis of India's progress towards implementing maternal health initiative, and of cultural and socio political factors which may be influencing this progress.